Supply-chain management capabilities practices in industrial organization in republic of Yemen - Abu Al- Rejal, Hussein Mohammed Esmail; D. Abu Doleh, Jamal; Mohtar, Shahimi (ExcelingTech Publishers, 2017)
Supply chain management play major role in performing manufacturing tasks inside and strength collaboration among suppliers and customers. In this paper, the main aims is to examine the level of Supply Chain Management Capabilities (SCMC) practicing in manufacturing in Yemen. To achieve this objective, geographical clustered sample was employed, Thirty nine manufacturing were surveyed in five governorates, top and middle managers were asked to answer the questionnaire. To measure the level of SCMC practice, descriptive and standard deviation employed. The findings show high level of practice and supported with consistency in deviation.